On the rheological properties of multi-walled carbon nano-polyvinylpyrrolidone/silicon-based shear thickening fluid - Sun Li (De Gruyter, 2021)
This study examines the rheological properties of shear thickening fluid (STF) enhanced by additives such as multi-walled carbon nanotubes (MWCNTs), polyvinylpyrrolidone (PVP), and nano-silica (SiO2) at different mass fraction ratios. The rheological properties of the liquid (MWCNTs–PVP/SiO2–STF) and the effect of the rheological properties of the STF under different plate spacing of the rheometer were investigated. The optimal mass fraction mixing ratio was also studied. The MWCNTs–PVP/SiO2–STF system with different PVP mass fractions was fabricated using ultrasonic technology and the mechanical stirring method. Then, the steady-state rheological test of the MWCNTs–PVP/SiO2–STF system was carried out with the aid of the rheometer facility. Dynamic rheological and temperature sensitivity tests on the MWCNTs–PVP/SiO2–STF system with 0.1 and 0.15% PVP mass fractions were performed. The rheological test results show that the MWCNTs–PVP/SiO2–STF system has a significant shear thickening effect when the PVP mass fraction is increased from 0 to 0.15%. When the PVP mass fraction is 0.1% and the plate spacing is 1 mm, the system exhibits the best shear thickening performance. This is based on the following facts: the viscosity can be achieved as 216.75 Pa s; the maximum energy storage and energy consumption capabilities can be observed. As a result, PVP can significantly enhance the shear thickening performance of the MWCNTs/SiO2–STF system.